RECONSTRUCTION OF THE ISLAMIC SCIENCE PARADIGM: COMPARATIVE STUDY OF KUNTOWIJOYO AND ZIAUDDIN SARDAR'S PERSPECTIVES - Lahuddin, Mukhlishina; Romadhon, Ahmad (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Amidst the rapid pace of global modernization, reconciling modern science with Islamic values has emerged as a pivotal theme. The reconstruction of the paradigm of Islamic science represents a significant intellectual endeavor aimed at addressing this crucial issue. It offers profound insights into the inseparability of science and religion, demonstrating their potential to mutually enhance the pursuit of universal truth. The research method used is library research, conducting a comparative study of two prominent thinkers, Kuntowijoyo and Ziauddin Sardar, who hold unique perspectives on the role of science within the Islamic context. Kuntowijoyo, deeply rooted in Indonesian traditions, provides a distinctive viewpoint in linking science with Islam, as articulated in his work "Islam as a Science, Epistemology, Methodology and Ethics." Conversely, Ziauddin Sardar offers an intricate narrative that traces the intricate interplay between modern science and Islamic scholarly traditions. By juxtaposing these two perspectives, this research aims to unravel their views on the reconstruction of the paradigm of Islamic science. The research highlights their perspectives on the reconstruction of the Islamic science paradigm, discusses the convergence of key elements of Islam and science, and reveals the intersection of Indonesia's intellectual tradition and global perspectives in shaping this paradigm. This study provides insights into the critical contributions of Kuntowijoyo and Ziauddin Sardar in advancing the discourse of Islam in the context of contemporary science.